A Juridical Analysis of Constitutional Court Decision No. 135/PUU-XXII/2024: The Separation of National and Regional Elections from a Constitutional Perspective - Muhammad Fahmi Islami (Yayasan Cerdas Pedia Indonesia, 2025)
This article presents a comprehensive juridical analysis of Constitutional Court Decision No. 135/PUU-XXII/2024, which mandates the separation of national and regional elections in Indonesia. Article 22E of the 1945 Constitution, previously interpreted to require simultaneous elections every five years, is here redefined under a “living constitution” approach to allow staggered ballots. Employing a normative-juridical method, the study examines (1) the Court’s interpretive shift and its alignment with theories of judicial activism, (2) institutional dynamics created by MK’s role as a positive legislator, and (3) practical implications for Indonesia’s presidential system and electoral management. Key technical terms judicial activism (court‐driven policy innovation), living constitution (dynamic constitutional interpretation), and electoral governance (framework of rules and practices for elections) are defined early to aid international readers. The analysis integrates comparative insights from other democracies and expert perspectives, including critiques from Simon Butt on potential judicial overreach and Titi Anggraini on the midterm election paradox. Findings reveal that while separation enhances administrative efficiency and issue-focused campaigns, it also engenders significant challenges: legislative vacuums in transition, risks to executive stability through unscheduled “midterm” referenda, and possible declines in voter engagement in off-cycle polls. The study’s novelty lies in its interdisciplinary framework combining constitutional theory, institutional analysis, and policy evaluation and the development of a “Constitutional Electoral Governance Model” to guide future reforms. By distilling complex legal arguments into core results, this research offers an original contribution to constitutional law scholarship and provides actionable insights for democratic law reform in Indonesia.